In vitro signal transduction mechanism exerted by 2-ethyl-3-O-sulphamoyl-estra-1,3,5(10),15-tetraen-3-ol-17-one in combination with dichloroacetic acid on breast adenocarcinoma (MCF-7) and breast non-tumorigenic (MCF-12A) cells - Joubert, Annie M. (University of Pretoria, 2015)
Thesis (PhD)--University of Pretoria, 2014.